Thermal and Flow Characteristics of Discrete Double Inclined Ribs at Low Curvature Coil for GSHP Application - Teguh Hady Ariwibowo; Keishi Kariya; Akio Miyara (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2020)
In this study, the thermal and hydraulic characteristics in low curvature coil with Discrete Double Inclined Ribs (DDIR) were investigated. Water is selected as a working fluid, and flowrate range from 1 to 5 L/min, which is a low flowrate condition. Effect of geometry parameters such as distance between ribs, curvature ribs, and ribs inclination angles was observed. Results obtained by numerical simulations show that the heat transfer in DDIR-coil is 7.7 to 29.11% greater than that in plain coil, while the pressure drop was approximately 12.7 to 89.5% larger than that of plain-coil. A COP improvement factor that is calculated based on energy loss by pressure drop and energy saving by heat transfer enhancement was found to vary between 0.25 and 5.29. Flow visualization shows that there are two vortexes in cross-section at the downstream, and local vortexes arise around the ribs of DDIR-coil, which shows similar pattern and strength to DDIR-straight tube. The vortex makes a long fluid particle path and strengthens the turbulent mixing between the wall and the core flow of the coil. Based on these findings, DDIR-coil is recommended for applications in Slinky Ground Heat Exchangers, especially at low flowrates.